Assessing the Characteristics of Rural Savings Systems and Their Impacts on Rural Livelihoods of Selected Districts of Sierra Leone - Ngegba , Mohamed Paul; Kamara, James; Koroma , Muctar Foday (Research Highlights in Agricultural Sciences Vol. 4, 2022)
Rural community savings systems are the most expected self-help groups in African, Asian, Caribbean, and Indian countries. Rural Community Savings systems are one of the solutions to empowering their members to generate more income in many parts of West African countries. This study attempts to assess the characteristics of rural community savings systems and their impacts on rural livelihood in selected districts of Sierra Leone. The researchers adopted three objectives, (1) identify the personal and socio-demographic characteristics of rural dwellers (savings members and non-savings members) that influence participation in rural community savings systems, and (2) identify the factors, operational conditions and modalities of the savings systems, and (3) assess the impact of the rural community savings systems on the livelihood of rural dwellers in selected districts of Sierra Leone. The study adopted a cross-sectional design. The population consists of savings members and non-savings in Bo, Bombali and Kenema Districts. The population size was 897, of which 810 savings with an equivalent of 810 non-savings, giving a sample size of 1,620 rural dwellers. Two sets of pretested questionnaires and focus group guides with a reliability of 0.75 were administered using KoBoCollect v.1.14.0a software; analysed data using simple frequencies, logit regression and propensity score match models. Participation in the savings program positively impacted various rural community. The study reveals a positive and highly statistically significant relationship between the age of the savings member and their Participation in RCSS at a one percent significance level (P=0.008). All other things being constant, as the ages of the savings member increase, they are more likely to participate in the rural community savings system. Household size has a positive and statistically significant relationship with the probability of Participation in the RCSS (P=0.000) at a one percent significant level. This result reveals that as household size increases, their exposure to consumption shock also increases, making them more likely to use microfinance resources to normalize their exposure to shocks and risks. Respondents' livestock ownership showed a positive and statistically significant relationship with the probability of participating in savings groups at a 5 percent significance level (P=0.008). In the logit regression, contrary to expectations, microenterprises' ownership had a statistically significant negative probability of borrowing from savings groups. Respondents owning microenterprises were fewer borrowers. Moreover, they participate more in savings groups compared to those who do not own microenterprises. The type of loan, livestock ownership, and receipt of income from temporary employment affect participation. Participants' access to electricity, microenterprise ownership, and adversative events significantly influence the decisions to participate in savings groups. Rural community savings systems should conduct basic training on savings and financial management within their communities to raise awareness. 2. Rural community savings groups should conduct in-service training programmes to fully explain the guiding characteristics of the operations of the rural community savings systems. Operational modalities are appropriately monitored for their efficacy and let membership be committed to guiding roles of the savings groups in achieving the main objectives. 3. The savings system should set out sharing time to enable members to use their share outs best and make more efforts to cater for those categories of rural dwellers, reducing the dependency rate within the rural communities. 4. The rural community savings systems should strategize to include many non-saving members in the organisation, and implementation programmes should, on a large scale, address the fundamental financial intermediation of the rural communities in Sierra Leone.